2018
DOI: 10.1155/2018/1027831
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Accessory Nerve Duplication: A Case Report and Literature Review

Abstract: Aim of the present study is to expand our knowledge of the anatomy of the 11th cranial nerve and discuss the clinical importance and literature pertaining to accessory nerve duplication. We present one case of duplicated spinal accessory nerve in a patient undergoing neck dissection for oral cavity cancer. The literature review confirms the extremely rare diagnosis of a duplicated accessory nerve. Its clinical implication is of great importance. From this finding, a further extension to our knowledge of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…A review of the literature has reported numerous cases of 6th and 11th cranial nerve anomalies; however, there remains only one other documentation of a 10th cranial nerve duplication in a 2019 case report. [1][2][3][4] The only other duplicate vagus nerve documentation discussed two nerves in an accessory setting unequal in size to each other. 5 In our case, the identical nerves needed to be differentiated for VNS placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature has reported numerous cases of 6th and 11th cranial nerve anomalies; however, there remains only one other documentation of a 10th cranial nerve duplication in a 2019 case report. [1][2][3][4] The only other duplicate vagus nerve documentation discussed two nerves in an accessory setting unequal in size to each other. 5 In our case, the identical nerves needed to be differentiated for VNS placement.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature has reported numerous cases of 6th and 11th cranial nerve anomalies; however, there remains only one other documentation of a 10th cranial nerve duplication in a 2019 case report. 1 2 3 4 …”
Section: Discussionmentioning
confidence: 99%